2018
DOI: 10.21873/anticanres.12207
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Nicotinamide N-Methyltransferase and Gap Junction Protein Alpha-1 Causes Metastasis in Adenoid Cystic Carcinoma

Abstract: NNMT is a potential biomarker of AdCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This observation is supported by single-cell gene expressing data, showing the highest NNMT expression levels in the ccRCC tumour compartment. Eckert et al and several other studies identified NNMT as a metastasis-associated gene, [54][55][56][57] possibly acting by inducing the expression of matrix-metalloproteinase 2 (MMP-2) 8 and maintaining dedifferentiated mesenchymal-like gene expression. 13,58 In agreement, we observed deregulated metastasis-associated genes in NNMT kd knockdown cells in our study, including MMP-13, laminin subunit gamma 2 (LAMC2) and alpha-1,6-mannosylglycoprotein 6-beta-Nacetylglucosaminyltransferase (MGAT5).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is supported by single-cell gene expressing data, showing the highest NNMT expression levels in the ccRCC tumour compartment. Eckert et al and several other studies identified NNMT as a metastasis-associated gene, [54][55][56][57] possibly acting by inducing the expression of matrix-metalloproteinase 2 (MMP-2) 8 and maintaining dedifferentiated mesenchymal-like gene expression. 13,58 In agreement, we observed deregulated metastasis-associated genes in NNMT kd knockdown cells in our study, including MMP-13, laminin subunit gamma 2 (LAMC2) and alpha-1,6-mannosylglycoprotein 6-beta-Nacetylglucosaminyltransferase (MGAT5).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that investigated the activity and the biological role of NNMT, found high NNMT mRNA and protein levels and high catalytic activity in different cancer cell lines, including LSCC cell lines [ 34 ], ESCC cell lines EC9706 and TE1 [ 13 ], and PTC cell line BHP 2-7 [ 39 ]. Moreover, NNMT upregulation from low tumorigenic to the highly metastatic AdCC cell lines was demonstrated [ 35 ]. These studies also explored the involvement of NNMT on modulating cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The microarray analysis demonstrated that NNMT expression was 2.0 times higher in ACCS-LN-GFP than in ACCS-metastatic-GFP cells (ACCS-M-GFP). Furthermore, the NNMT mRNA and NNMT protein levels of ACCS-M-GFP, and even more of ACCS-LN-GFP, were significantly higher compared to those in the ACCS-GFP cell line [ 35 ]. This data supports the critical role of NNMT in AdCC invasion and metastasis.…”
Section: Other Tumors Of Maxillo-facial Regionmentioning
confidence: 99%
“…In some instances, it has been observed that CSCs have low expression of connexin genes and exhibit low GJIC (e.g., [123][124][125]; see also reviews on the topic [125,126]). This is supported by some observations in CSCs or CSC-like cells from glioma [127,128], liver cancer [129,130], lung cancer [131,132], triple-negative breast cancer [76], and adenoid cystic carcinoma [133]. However, other studies have shown the presence of GJIC in glioblastoma [33,134], gastric cancer [135], lung cancer [136], and breast cancer [137,138].…”
Section: Cancer Stem Cellsmentioning
confidence: 63%